2019
DOI: 10.1002/app.47828
|View full text |Cite
|
Sign up to set email alerts
|

A compatible and crosslinked poly(2‐allyl‐6‐methylphenol‐co‐2,6‐dimethylphenol)/polystyrene blend for insulating adhesive film at high frequency

Abstract: A polymer blend consisting of poly(2‐allyl‐6‐methylphenol‐co‐2,6‐dimethylphenol) (APPE) and polystyrene (PS) with additives such as 1,2‐bis(4‐vinylphenyl)ethane, cyanate ester, and nitrile butadiene rubber was formulated as an insulating high‐frequency adhesive film. The polymer blend of APPE and PS showed very high compatibility to these additives, and the resulting thermally cured polymer blend exhibited an excellent mechanical strength, as shown by an ultimate tensile strength of 51 MPa and Young's modulus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…To improve a signal transmission rate, signal integrity and prevent signal distortion arising from the dielectric loss, materials with low D k and D f values at a high-frequency are highly demanded. Many low D k polymers have been reported, , such as polyimides (PI), poly­(phenylene ether) (PPE), benzocyclobutene (BCB) resins, , poly­(silsesquioxane), fluoropolymers, , and polynaphthalene. , Among them, PIs have attracted broad attention due to their excellent physical properties including thermal stability, high resistance to chemicals, and mechanical properties …”
Section: Introductionmentioning
confidence: 99%
“…To improve a signal transmission rate, signal integrity and prevent signal distortion arising from the dielectric loss, materials with low D k and D f values at a high-frequency are highly demanded. Many low D k polymers have been reported, , such as polyimides (PI), poly­(phenylene ether) (PPE), benzocyclobutene (BCB) resins, , poly­(silsesquioxane), fluoropolymers, , and polynaphthalene. , Among them, PIs have attracted broad attention due to their excellent physical properties including thermal stability, high resistance to chemicals, and mechanical properties …”
Section: Introductionmentioning
confidence: 99%
“…As of now, various polymers with excellent dielectric properties have been reported, such as polyphenylene ether (PPE), [ 24,25 ] polystyrene (PS), [ 26,27 ] and fluoropolymers. [ 28 ] Unfortunately, it can not be well used because of the limitations of its thermal and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…It has been confirmed that the introduction of low dipole moment groups and the reduction of the density of the imide group are effective methods to reduce D f . [22,23] As of now, various polymers with excellent dielectric properties have been reported, such as polyphenylene ether (PPE), [24,25] polystyrene (PS), [26,27] and fluoropolymers. [28] Unfortunately, it can not be well used because of the limitations of its thermal and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a polymer network with a low D k value can increase signal propagation speed. Many low-dielectric polymers have been reported in the literature. Among them, poly­(2,6-dimethyl-1,4-phenylene oxide) (PPO) , has been extensively studied due to its special characteristics such as low polarity, high T g , low dielectric properties, and so forth. However, PPO also has some disadvantages, for example, properties like high melting point, limited solubility, and high viscosity, leading to their limited applications in copper-clad laminate industry.…”
Section: Introductionmentioning
confidence: 99%